Report on Farmers’ Field Days at Adami Tulu Jido Kombolcha and Bako Tibe Districts in 2017 - Tesfaye, Kindie (2018)
Integrated assessment of the determinants of the maize yield gap in Sub- Saharan Africa: towards farm innovation and enabling policies (IMAGINE) Bringing CSA practices to scale: assessing their contributions to narrow nutrient and yield gaps (Crop Nutrient Gap) Field Demonstration Day of Nutrient Management Packages – On Farm Demonstration Trials in Ethiopia